Institutional determinants of labour market outcomes in the EU: A social model employment efficiency and income distribution index - Michael Knogler; Fidelis Lankes (Institut für Ost- und Südosteuropaforschung (IOS), 2015)
Labour market performance as measured by employment rates conceals significant differences among EU countries. In 2014 the variation was between 48.8% in Greece and 74.4% in Sweden. Average employment rate for the EU28 was at 64.8% in 2014, perceptibly below the Lisbon goal of 70 percent. Inequality in income distribution as measured by S80/S20 income quintile share ratio ranges in 2013 from 3.4 in Czech Republic to 6.6 in Bulgaria, Romania and Greece and has risen especially in Southeast European countries during the last years. To some extent, labour market and social institutions may account for these differences. Implemented social models in Europe differ from each other by different combinations of policies and institutions showing the dimensions of social models. We use these dimensions to develop two indices which capture the employment and income distribution efficiency of social models i.e. shows how institutions impact on employment and income distribution. Both indices can be used to rank and compare the institutional quality of social models across EU countries.
urn:nbn:de:101:1-201510282801
Keywords: I30; J50; P51; 330; european social models; labour market institutions; employment; income distribution